F-J-semi Regular Modules - Turki , Lewaa R.; Khalid, Wasan (Iraqi Journal of Science, 2022)
Let be a ring with identity and let be a left R-module. If is a proper submodule of and , is called –semi regular element in , If there exists a decoposition such that is projective submodule of and . The aim of this paper is to introduce properties of F-J-semi regular module. In particular, its characterizations are given. Furthermore, we introduce the concepts of Jacobson hollow semi regular module and –semiregular module. Finally, many results of Jacobson hollow semi regular module and –semiregular module are presented.